Study of the gender difference of young's value attitude of own health and healthy life: The work was supported by the Science Committee of RA, in the frames of the research project № 21T-5C177 - Hovhannisyan, Sahak (Bulletin of Yerevan University E: Philosophy, Psychology, 2022)
The process of creating health-care technologies and introducing healthy life (HLS) into the daily life of modern youth implies a comprehensive solution of the number of research problems. The results of the survey and its analysis aimed at identifying gender differences in the value attitude of Russian-Armenian (Slavonic) University students to their own health and a healthy life is presented in this article. A comparative analysis of the obtained indicators revealed that young female students show a more conscious, responsible and consistent attitude towards their own health and various aspects of a healthy life than male students.
Keywords: health; healthy life; state of health; questionnaire survey; value attitude; gender differences; health-care technologies